La documentación como fuente de información para la restauración arquitectónica = Documentation as Information Source for the Architectural Restoration - Rivas Quinzaños, Pilar (Revista electrónica ReCoPar, 2006)
Abstract Documentation, understood in an wide sense, is the basic source of information for any historic research performed on Histroric Heritage. At the same time, it serves as the supporting ground for the scientific base of any Historic Report of a building to be restored or declared as a good of cultural interest. This article establishes a working methodology of research for developing Historic Reports about Architectural Heritage and offers an outline for this type of survey. In addition, it includes specific bibliogragy to help enhancing the study topic.